KALIMAT IMPERATIF DALAM BAHASA JAWA - Nuryani Nuryani (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2014)
The language system in this world has universality. It means, every language has some element in common. As in the case of the structure of the sentence or sentences diversity. Javanese language has a diversity sentence similar to other languages. There is imperative sentence or order sentence in Javanese language. This sentence is spoken by speakers in order to get a reaction or response from the opponent speaker. Responses are expected to both verbal and nonverbal. The data taken from the mass media such as magazine or newspaper that is written by Javanese language. In addition, the data is also collected verbally from informants and other data generated creativelly by the writer as native speaker of Javanese language. The results obtained are, there are five characteristics that mark imperative sentence in the Javanese language, namely (1) the written sentence marked with (!), (2) the oral sentence intonation pattern [2] 3 # or [2] 3 2 # , (3) ended by -en, -a, -ana, or -na on his P, (4) can be given a pointer word commands like